The haunted castle - Cernuschi, Claudio; Grassini, Valentina, 1981-; Heim, Julia (Geronimo Stilton, 2011)
Uncle Samuel S. Stingysnout invites the whole Stilton family to creepy, faraway Penny Pincher Castle for a big surprise.